Psychology of Education of Teenagers in the Spirit of Military Patriotism - Rashidov Khurshid Urinbayevich (Researchparks Publishing, 2022)
In this article, ideas are put forward about educating young students in the spirit of military patriotism. It is known to everyone that educating young people, who are the future of the state, with high moral qualities, humane, physically strong, patriotic, with military knowledge, in the spirit of national pride, is the most urgent issue of today. This article can be used by relevant industry representatives.